Ireland's pre‐1940 daily rainfall records. (16th August 2020) - Ryan, Ciara; Murphy, Conor; McGovern, Rhonda; Curley, Mary; Walsh, Séamus; ,
Abstract: This article presents daily rainfall data and metadata for Ireland transcribed from historical manuscript and printed copies of rainfall registers located in Met Éireann's archives. To facilitate the transcription of rainfall observations from paper records, the historical manuscripts were scanned and integrated into Met Éireann's digital archives. The transcription from digital image to data format was undertaken in collaboration with students at Maynooth University as part of a novel crowdsourcing initiative to integrate data rescue activities into the classroom. In total, 3, 616 station years of rainfall data (~1.32 million daily values) were transcribed. The data, which was double keyed, have undergone basic quality assurance to check for transcription errors and the resultant raw data and associated metadata are presented here. Ongoing work involves the application of further quality assurance and homogenization techniques to develop a long‐term, quality assured daily rainfall network for Ireland. Abstract : Daily rainfall data and metadata for Ireland transcribed from historical manuscript and printed copies of rainfall registers located in Met Éireann's archives. In total, 3, 616 station years of rainfall data (~1.32 million daily values) were transcribed. The data, which was double keyed, has undergone basic quality assurance to check for transcription errors. Ongoing work involves the application of further quality assurance and homogenisation techniques to develop a long‐term, quality assured daily rainfall network for Ireland.